2011
DOI: 10.1155/2011/594645
|View full text |Cite
|
Sign up to set email alerts
|

In Critically Ill Patients, Serum Procalcitonin Is More Useful in Differentiating between Sepsis and SIRS than CRP, Il-6, or LBP

Abstract: We studied the usefulness of serum procalcitonin (PCT), interleukin-6 (IL-6), lipopolysaccharide binding protein (LBP) levels and C-reactive protein (CRP) levels, in differentiating between systemic inflammatory response syndrome (SIRS) and sepsis in critically ill patients. Methods. In this single centre prospective observational study we included all consecutive patients admitted with SIRS or sepsis to the ICU. Blood samples for measuring CRP, PCT, IL-6 and LBP were taken every day until ICU discharge. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 14 publications
2
79
1
2
Order By: Relevance
“…Trotz dieser Einschr ä nkung zeigen viele Studien, dass Spezifi t ä t und Sensitivit ä t der PCT-Spiegel f ü r die Diagnose einer bakteriellen Infektion h ö her als die anderer Parameter wie zum Beispiel den immer noch am h ä ufi gsten genutzten CRP-Spiegeln oder den Leukozytenzahlen sind [24] . Auch konnte in neueren Studien gezeigt werden, dass PCT-Spiegel besser in der Lage sind zwischen SIRS und Sepsis zu unterschieden als CRP, IL-6 und LBP-Plasmaspiegel [10,25] . Insgesamt weisen die vorliegenden Daten darauf hin dass ein Anstieg der PCT-Spiegel bei einem Risikopatienten auf Intensivstation als Verdacht auf eine zugrunde liegende oder beginnende Infektion gewertet werden muss und auf jeden Fall weiter abgekl ä rt werden muss.…”
Section: Klinische Anwendung Der Pct-spiegel Infektionsmarkerunclassified
See 1 more Smart Citation
“…Trotz dieser Einschr ä nkung zeigen viele Studien, dass Spezifi t ä t und Sensitivit ä t der PCT-Spiegel f ü r die Diagnose einer bakteriellen Infektion h ö her als die anderer Parameter wie zum Beispiel den immer noch am h ä ufi gsten genutzten CRP-Spiegeln oder den Leukozytenzahlen sind [24] . Auch konnte in neueren Studien gezeigt werden, dass PCT-Spiegel besser in der Lage sind zwischen SIRS und Sepsis zu unterschieden als CRP, IL-6 und LBP-Plasmaspiegel [10,25] . Insgesamt weisen die vorliegenden Daten darauf hin dass ein Anstieg der PCT-Spiegel bei einem Risikopatienten auf Intensivstation als Verdacht auf eine zugrunde liegende oder beginnende Infektion gewertet werden muss und auf jeden Fall weiter abgekl ä rt werden muss.…”
Section: Klinische Anwendung Der Pct-spiegel Infektionsmarkerunclassified
“…Die Spezifi t ä t und der positive pr ä diktive Wert zur Erkennung einer Infektion liegen in den meisten Untersuchungen bei > 80 % und damit ü ber denen anderer biochemischer Marker [10,11,50,51] . Allerdings ist zu ber ü cksichtigen, dass auch andere Erkrankungen zum Anstieg der zirkulierenden PCT-Spiegel f ü hren k ö nnen.…”
Section: Zusammenfassende Bewertungunclassified
“…In particular, extensive clinical evidence indicates that PCT is a biomarker for both follow-up and evaluation of the effectiveness of antibiotic therapy for severe respiratory infections and sepsis; in all relevant guidelines, the use of PCT in this context is categorized as evidence class 2B or 2C [3,4]. For example, PCT levels differentiate more effectively between sepsis and systemic inflammatory response syndrome (SIRS) than those of IL-6, IL-8, or CRP [5,6]. A meta-analysis of several clinical studies of various infections demonstrated that PCTguided antibiotic therapy reduced both therapy duration and the length of stay in intensive care [7].…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…Several studies have evaluated the diagnostic utility of various biomarkers, including ferritin, haptoglobin, interleukin 6, C-reactive protein (CRP), and procalcitonin (PCT), for suspected sepsis in the ICU patient population (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). PCT has been the most-well-studied biomarker and has demonstrated the most promising results to date in the diagnosis of bacterial infection in a number of settings (16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…However, recent meta-analyses have suggested that PCT alone may be insufficient to accurately differentiate bacterial from nonbacterial sepsis or other causes of SIRS (22)(23)(24). Similarly, previous studies assessing the use of PCT alone or in comparison to other biomarkers for the diagnosis of sepsis have had variable performance characteristics (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), likely due to differences in patient populations, the type of assay performed, the timing of sample testing, the selection of cutoff values, and the selection of the gold standard for determining sepsis.…”
mentioning
confidence: 99%